Analisis Pengaruh Penggunaan Leaflet Syariah Terhadap Kepatuhan Minum Obat Pasien Hipertensi Di Puskesmas Gunung Pati Kota Semarang Tahun 2024 - Rini, Tri Diana Puspita; Asti Erniawati, Winda; Eliza, Diah Ayu (Sultan Agung Islamic University of Semarang, 2025)
Background: Hypertension is a chronic disease that occurs sometimes without symptoms and is still a problem with the increasing number of patients affected by hypertension. There are still many hypertensive patients who are non compliant with their treatment. They think that when they take medication they will be cured, even though antihypertensive medication must still be taken to keep blood pressure under control, so education needs to be carried out using sharia leaflets with Islamic elements which can later help increase patient compliance and always pray, be patient and trust in undergoing treatment. Methods: The research method uses Quasi Experimental which compares the intervention group and the control group with a Pre-test and Post-test design using the MMAS-8 questionnaire to determine the patient's level of medication adherence. Results: There was a significant difference in the level of adherence to taking medication for hypertensive patients in the control group and the intervention group using the Islamic Sharia questionnaire with a p-value of 0.021 < 0.05 and using the MMAS-8 questionnaire, a p-value of 0.005 < 0.05 was obtained. Conclusion: It is said that there is an effect of giving sharia leaflets to prolanis patients at the Gunung Pati Community Health Center, Semarang City in 2024 with a P-value of 0.000 < 0.05